Dolphins in danger - Lumry, Amanda; Hurwitz, Laura; McIntyre, Sarah (Bellevue, WA : Eaglemont Press, 2005)
Riley helps save a pod of dolphins that become trapped in a lagoon in Tahiti.
Keywords: Wildlife rescue -- Fiction; Spinner dolphin -- Fiction; Dolphins -- Fiction; Marine animals -- Fiction; Scientists -- Fiction; Tahiti (French Polynesia : Island) -- Fiction